Tingkat Kepuasan Pasien Rawat Inap Dan Keluarga Pada Pelayanan Keperawatan Di Rumah Sakit DKT Mojokerto - Asrul Anam; Ika Khusnia (LPPM Sekolah Tinggi Ilmu Kesehatan Majapahit Mojokerto, 2019)
Patient satisfaction is the patient's feelings that arise due to the performance of health care that is obtained after comparing with their perceived, so it is necessary to clear efforts from the hospital to provide a conceptual and integrated services to ensure patient satisfaction, but it is not easily earned. One way is to improve the performance of nurses. Research purpose to determine the level of satisfaction of inpatients and their families in nursing care in DKT Mojokerto Hospital. This is a descriptive research design using public opinion survey. The variable in this study is a single variable the level of satisfaction of inpatients and their families in nursing care in DKT Mojokerto Hospital. The population in this study were all patients hospitalized in DKT Mojokerto Hospital. The technique sampling use total sampling technique with a sample of 35 patients and 35patients families. The study was 12 - 28 February 2011 in DKT Mojokerto Hospital. Technique and instrument data collection using questionnaires. Having collected data were analyzed by using the formula linkert scale. The results obtained more than 50% of patients expressed satisfaction on the inpatient nursing service as many as 18 respondents (51.4%), while the rest are not satisfied. More than 50% of the families of inpatients expressed his satisfaction at the nursing service that is as much as 19 respondents (54.3%). Customers and their family have same proportion that they felt satisfaction about nursing services. It means that they got same services from nurse. Customers in nursing services not only patients but also patients' families to consider. Therefore, when the family also felt satisfied, others would follow them, so that the daily coverage in DKT Mojokerto Hospital could increase.